Mobile Web Application for Grocery Budget Planning - Qurratul-Ain, Abdullah; Johari, Abdullah (Faculty of COmputer Science and Information Technology, 2015)
Grocery shopping can be a real hassle, especially for shoppers with specific preferences, or an interest in saving money. In recent years, the basic shopping list has evolved into a variety of tools and mobile applications, each with different improvements over the classic pen and paper version. In this project, a mobile web application that consolidates all the available information and tools into a single, intuitive shopping assistant, providing price comparison across different brands and stores, all focused around a customizable list of needed items. The effectiveness of our solution will be evaluated by analyzing through online surveys and data gathered from willing users on the effects of the app on their habits and spending. This mobile app will have the potential to benefit everyone who grocery shops, in particular those people with financial concerns.